[PP.21.08] PLASMA VASCULAR ENDOTHELIAL GROWTH FACTOR TYPE C CONCENTRATION AS THE MODULATOR OF THE RELATION BETWEEN URINARY SODIUM EXCRETION AND BLOOD PRESSURE IN HUMANS. (September 2016) - Bednarski, A.; Stolarz-Skrzypek, K.; Kloch-Badelek, M.; Franczyk, A.; Kielbasa, G.; Kawecka-Jaszcz, K.; Czarnecka, D.
Abstract : Objective: Vascular endothelial growth factor type C (VEGF-C) is a novel marker of sodium accumulation in subcutaneous tissue, not yet explored in humans. The animal studies have demonstrated significant correlation between excess sodium intake, increase in plasma VEGF-C and high blood pressure. The aim of the study was to investigate the relation between sodium intake, plasma VEGF-C concentration and blood pressure in high salt intake population. Design and method: The study group included 198 subjects recruited from the general population of Southern Poland, never treated with antihypertensive medications. Ambulatory blood pressure (ABP) monitors (SpaceLabs 90207) were programmed to obtain measurements each 15 min during the day (6.00–22.00) and each 30 min nighttime. Sodium intake was assessed based on 24-hour urinary sodium excretion. The plasma VEGF-C concentration was measured using ELISA kit in certificated laboratory. Database management and statistical analysis were performed with SAS software (SAS Institute, Cary, NC), version 9.3. Results: The study group included 91 men and 107 women, mean age 40.3 years, office BP 124.8/84.2 mmHg, 24hUVNa 162 mmol/24 h and mean serum VEGF-C concentration 1238 pg/ml. The analyses were adjusted for age, sex, BMI, antihypertensive treatment, smoking, CRP, sodium excretion and alcohol intake. We observed negative association between serum VEGF-C concentration and both SBP (r -0.0017 p 0.0473) and DBP (r -0.0014 p 0.0491) over 24 h. Conclusions: In our high salt intake population, plasma VEGF-C concentration was negatively related to systolic and diastolic blood pressure on 24-hour ambulatory monitoring in multivariate models. Effective subcutaneous sodium accumulation, indirectly represented by plasma VEGF-C, might prevent increase of blood pressure in high salt intake individuals.